THE EFFECT OF PIPER CROCATUM LEAVES TO GLUCOSE SERUM LEVEL - -, Budiman (Majority, 2015)
Abstract Diabetics in Indonesia continues to increase. Based on data from the World Health Organization (WHO), Indonesia is the fourth country in the world after the United States, India, and China, whose population is a lot of suffering from diabetes. WHO predicts rise in diabetes from 8.4 million in 2000 to 22 million by 2030. There are several chemical constituents in red betel leaf , including karvakrol , eugenol , saponins , polyphenols and flavonoids . Flavonoids and polyphenols are antioxidants, so have antihyperglycemic activity .This experiment was an laboratoric experimental research with pretest and posttest control group design. Statistical analysis results showed a decrease in blood glucose levels were significant in the positive control group, the dose of piper crocatum extract I, II, III, and there are significant differences between the groups premises distilled piper crocatum extract. Red betel leaf extract against alloxan-induced rats decreased blood glucose levels were significantly (p <0.05). Keywords : Alloxan, Diabetes, Glucose, Piper Crocatum Abstrak Penderita diabetes di Indonesia terus meningkat. Berdasarkan data dari Organisasi Kesehatan Dunia (WHO), Indonesia merupakan negara keempat di dunia setelah Amerika Serikat, India, dan China yang penduduknya banyak menderita diabetes. WHO memprediksi kenaikan angka diabetes dari 8,4 juta pada tahun 2000 menjadi 22 juta pada tahun 2030. Terdapat beberapa kandungan kimia didalam daun sirih merah, diantaranya karvakrol, eugenol, saponin, polifenol dan flavonoid. Senyawa flavonoid dan polifenol bersifat antioksidan, sehingga memiliki aktivitas antihiperglikemik. Penelitian yang akan dilakukan ini merupakan penelitian eksperimental laboratorik dengan pretest dan posttest dengan desain grup kontrol. Hasil analisis statistik menunjukkan adanya penurunan kadar glukosa darah yang bermakna pada kelompok kontrol positif, ekstrak daun sirih merah dosis I,II,III serta terdapat perbedaan yang signifikan antara kelompok aquades denga ekstrak daun sirih merah. Pemberian ekstrak daun sirih merah terhadap tikus putih yang diinduksi aloksan terjadi penurunan kadar glukosa darah yang bermakna (p<0,05). Kata kunci : Aloksan, Diabetes, Gula, Piper Crocatum